cGAS-like receptor-mediated immunity: the insect perspective. - Cai, H.; Meignin, C.; Imler, J.L. (Current Opinion in Immunology, 2022)
The cGAS-STING pathway plays a central role in the detection of DNA in the cytosol of mammalian cells and activation of immunity. Although the early evolutionary origin of this pathway in animals has been noted, its ancestral functions have remained elusive so far. We review here new findings in invertebrates establishing a role in sensing and signaling infection, triggering potent transcriptional responses, in addition to autophagy. Results from flies and moths/butterflies point to the importance of STING signaling in antiviral immunity in insects. The recent characterization of cGAS-like receptors in Drosophila reveals the plasticity of this family of pattern-recognition receptors, able to accommodate ligands different from DNA and to produce cyclic dinucleotides beyond 2'3'-cGAMP.